Study of Intestinal Worms in Children - Hamdi, Ruqaya Fadhil; Saddam, Abrar Ali; Ahmed, Hussein Ayad; Shahada, Yamam Rahman (American Journal of Biology and Natural Sciences, 2024)
Many children complain of stomach pain and this pain is not stable, but comes and goes. The more severe n is, the stranger symptoms appear, but they quickly disappear.